The importance of online exposure when applying for a job - Rosendo, M. I. (2017)
The rapid growth and development of information and communication technologies enabled the transition to a global and dynamic communication model. Among the many communication tools that have emerged, online social networks have proven to be the most popular. Its success has to do with the ability to converge several features into a single space, allowing users to share knowledge and experiences, maintain contact with their peers, as well as communicate freely and spontaneously. However, using these virtual platforms we are, inevitably, creating an online history that can affect our personal and professional lives. Facing a difficult and competitive job market, companies seek to capture the best talents, within their list of job candidates. In this context, companies are starting to screen online profiles to validate candidates’ personal characteristics in a non-professional environment. The main purpose of this study is to understand the importance of the activities in online social networks when applying for a job, especially among recent graduates, who are seeking their first professional experience. Results show that even though recent graduates take caution when using social networking sites, especially Facebook, online exposure is not considered an important factor when undergoing employment processes.